Forecasting Demand of Plastic in PT. Lowell Pack to Maximize the Profit - Tan, Christopher Russell; Chaerudin, Rendra (Journal of Business and Management, 2016)
Abstract. Plastic has growth very rapidly in South East Asia. This make local plastic factory have to manage the produce they can make to maximize the profit the company can get, PT Lowell pack, as case study because PT Lowell pack is the new plastic factory and the capacity is quite much for small factory about 90 ton. This research found that in PT Lowell pack have produce with same capacity in 3 products. They have even thought if they produce more in one product than another they can make more profit. This situation is happened because they are only using judgmental decision by the owner to forecast the demand and produce the product in PT Lowell pack. And Judgmental decision cannot give accurate prediction. Therefore, there area lot of mismatches between supply and demand. Because thatÂ  we have to know the best forecast method for demand plastic in PT Lowell pack and organize the produce per month per product to maximize the profit. And forecasting method we will use are Moving Average, Exponential Smoothing, Holt, trend analysis (regress over time).The research will search the best forecasting method to maximize the profit and The data which will be used is the secondary data from PT Lowell pack Sales report monthly by PT Lowell pack and profit report of PT Lowell pack monthly. These secondary data will be analysis further by forecasting method.so we can now the sales by PT Lowell pack monthly and maximize the profit PT Lowell pack monthly. And the result of this research PT Lowell pack have to choose to trend analysis method for forecasting. And have to produce more plastic kw2 after that kw1 after that Pure plastic. And PT Lowell pack get more profit if forecast the demand and get Rp13.077.500Keyword: forecasting, demand plastic in Indonesia, growing market plastic